Plasmodium malariae in Bangladesh. - Rahman, W; Chotivanich, K; Silamut, K; Tanomsing, N; Hossain, A; Faiz, M; Dondorp, A; Maude, R (2010)
We describe a 32-year-old Bangladeshi male presenting with severe malaria caused by a mono-infection with Plasmodium malariae. Rosetting of infected and uninfected erythrocytes, a putative virulence factor in falciparum malaria, was observed in the blood slide. Severe disease caused by P. malariae is extremely rare. The patient made a rapid recovery with intravenous quinine treatment.